DID IMPACTS, VOLCANIC ERUPTIONS, OR CLIMATE CHANGE AFFECT MAMMALIAN EVOLUTION? - Prothero D.R. (My University, 2004)
In recent years, it has become popular to attribute faunal change and mass extinction to impacts, volcanic eruptions, or climatic change. How well do these supposed causes compare to the excellent record of Cenozoic life, especially that of fossil mammals? Two different Cenozoic mammal diversity curves were compared, and important climatic, volcanic, and impact horizons were examined in detail. In no case is there a strong correlation between impacts, eruptions, or climatic events and any episode of mammalian turnover. On the contrary, most of the known impact, eruption, and climatic events of the Cenozoic occurred during intervals of faunal stability. Conversely, episodes of high turnover and faunal change among Cenozoic mammals correlate with no known extrinsic causes. Apparently, extrinsic environmental factors such as impacts, eruptions, and climate change have a minimal effect, and intrinsic biological factors must be more important.
Keywords: Cenozoic; Mammals; Evolution; Cenozoic; Кайнозой